Liposomal clodronate treatment for tumour macrophage depletion in dogs with soft‐tissue sarcoma. (27th April 2012) - Guth, A. M.; Hafeman, S. D.; Elmslie, R. E.; Dow, S. W.
Abstract : Increased numbers of tumour‐associated macrophages correlate with rapid tumour growth and metastasis in tumours. Thus, macrophage depletion has potential as a novel cancer therapy and positive responses have been reported in rodent tumour models. To investigate the effectiveness of this approach in dogs with cancer, we evaluated the effects of the macrophage‐depleting agent liposomal clodronate (LC) in dogs with soft‐tissue sarcoma (STS). To this end, we conducted a clinical trial of LC therapy in 13 dogs with STS. Repeated LC administration was well tolerated clinically. Preliminary examination of tumour biopsy sets from 5 of the 13 dogs demonstrated that the density of CD11b + macrophages was significantly decreased after LC treatment. Circulating concentrations of interleukin‐8 were also significantly reduced. These preliminary studies are the first to suggest that LC can be used as a systemic macrophage‐depleting agent in dogs to reduce numbers of tumour‐associated macrophages.